Sweet but sour: Impaired attention functioning in children with type 1 diabetes mellitus - Lancrei, Hayley M.; Yeshayahu, Yonatan; Grossman, Ephraim S.; Berger, Itai (Frontiers in Human Neuroscience, 2022)
Children diagnosed with type 1 diabetes mellitus (T1DM) are at risk for neurocognitive sequelae, including impaired attention functioning. The specific nature of the cognitive deficit varies; current literature underscores early age of diabetes diagnosis and increased disease duration as primary risk factors for this neurocognitive decline. Fourty-three children with T1DM were evaluated for ADHD symptomatology using the MOXO continuous performance test (MOXO-CPT) performed during a routine outpatient evaluation. The study cohort demonstrated a significant decline in all four domains of attention functioning. The effect was most pronounced with early age at T1DM diagnosis, a longer disease duration and with poorer glycemic control (represented by higher HbA1c values). With increased disease duration (of five plus years), acute hyperglycemia was associated with inattention in the real-time setting. These findings highlight the need for routine screening of neurocognitive function in children with T1DM so that early intervention can be employed during this crucial period of cognitive development.